Cultural grammars of nation, diaspora, and indigeneity in Canada - McCall, Sophie, 1969-; Kim, Christine, 1973-; Singer, Melina Baum, 1974- (TransCanada series., 2012)
Considers how the terms of critical debate in literary and cultural studies in Canada have shifted with respect to matters of race, nation, and difference.